2023
DOI: 10.1038/s41598-023-48008-5
|View full text |Cite
|
Sign up to set email alerts
|

A human bispecific antibody neutralizes botulinum neurotoxin serotype A

Jiansheng Lu,
Yujia Jiang,
Jiazheng Guo
et al.

Abstract: Botulinum neurotoxin (BoNT) shows high lethality and toxicity, marking it as an important biological threat. The only effective post-exposure therapy is botulinum antitoxin; however, such products have great potential for improvement. To prevent or treat BoNT, monoclonal antibodies (mAbs) are promising agents. Herein, we aimed to construct a bispecific antibody (termed LUZ-A1-A3) based on the anti-BoNT/A human monoclonal antibodies (HMAb) A1 and A3. LUZ-A1-A3 binds to the Hc and L-HN domains of BoNT/A, display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The neutralizing ability of anti-BoNT products are estimated in international units (IU), and 1 IU of antitoxin protects mice from 10000 × LD 50 BoNT/B ( 36 ). In our study, the antitoxin potency was calculated as IU/mg, 1 IU/mg means 1 mg antibody neutralize 10000 × LD 50 BoNT/B ( 37 ). The results showed that 0.66 µg of B20-hFc could provide 50% protection against 20 × LD 50 BoNT/B, the theoretically neutralization capacity was approximately 30300 × LD 50 /mg, which was the equivalent of 3 IU/mg; 0.5 µg of B14-hFc could provide 50% protection against 20 × LD 50 BoNT/B, the theoretically neutralization capacity was approximately 40000 × LD 50 /mg, which was the equivalent of 4 IU/mg; 0.28 µg of B12-hFc could provide 50% protection against 20 × LD 50 BoNT/B, the theoretically neutralization capacity was approximately 71000 × LD 50 /mg, which was the equivalent of 7 IU/mg; 0.2 µg of B5-hFc could provide 50% protection against 20 × LD 50 BoNT/B, therefore, the theoretical neutralization capacity was approximately 10 5 × LD 50 /mg, which was the equivalent of 10 IU/mg; and 0.1 μg of B9-hFc provided 50% protection in mice against 20 × LD 50 , indicating that B9-hFc had the strongest activity to neutralize the BoNT/B, and the theoretical neutralization capacity was about 2 × 10 5 × LD 50 /mg, which was the equivalent to 20 IU/mg.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The neutralizing ability of anti-BoNT products are estimated in international units (IU), and 1 IU of antitoxin protects mice from 10000 × LD 50 BoNT/B ( 36 ). In our study, the antitoxin potency was calculated as IU/mg, 1 IU/mg means 1 mg antibody neutralize 10000 × LD 50 BoNT/B ( 37 ). The results showed that 0.66 µg of B20-hFc could provide 50% protection against 20 × LD 50 BoNT/B, the theoretically neutralization capacity was approximately 30300 × LD 50 /mg, which was the equivalent of 3 IU/mg; 0.5 µg of B14-hFc could provide 50% protection against 20 × LD 50 BoNT/B, the theoretically neutralization capacity was approximately 40000 × LD 50 /mg, which was the equivalent of 4 IU/mg; 0.28 µg of B12-hFc could provide 50% protection against 20 × LD 50 BoNT/B, the theoretically neutralization capacity was approximately 71000 × LD 50 /mg, which was the equivalent of 7 IU/mg; 0.2 µg of B5-hFc could provide 50% protection against 20 × LD 50 BoNT/B, therefore, the theoretical neutralization capacity was approximately 10 5 × LD 50 /mg, which was the equivalent of 10 IU/mg; and 0.1 μg of B9-hFc provided 50% protection in mice against 20 × LD 50 , indicating that B9-hFc had the strongest activity to neutralize the BoNT/B, and the theoretical neutralization capacity was about 2 × 10 5 × LD 50 /mg, which was the equivalent to 20 IU/mg.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the neutralizing antibodies against botulinum neurotoxin have focused on serotype A ( 37 , 42 45 ). Numerous reports have described either murine or human BoNT/B-neutralizing antibodies ( 10 , 46 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations